Analytical Modeling and Experimental Characterization of Residual Resistance Loss of Broken Wire Ropes Lifting - Asmâa, Chouairi; Mohamed, El Ghorba; Abdelkader, Benali; El Mostapha, Boudlal; Abdelilah, Hachim; Khalid, El Had (Review of Energy Technologies and Policy Research, 2014)
The lifting wire ropes are hierarchically complex structures, very helpful and widespread in heavy manufacturing roofs, lifting systems, mining industry, offshore structure, electric lines, elevators, suspension bridges and transmission towers. Generally, the metallic cables structure provides solutions particularly interesting and spectacular to current problems faced by industries, which are called regularly to perform tasks for mechanical handling in steps of manufacturing product. The repetitive nature of these tasks, rather than decreasing the risk of accidents, helps to accentuate them by a sort of addiction to risk. In this context, the wire ropes are a prime target of brutal damage, compared to conventional structures. More generally; the sudden failure is the major cause of cables degradation. Industrial experience shows that the failure of much of their hoisting ropes in use is most commonly due to cumulative damage of wires. This is particularly insidious due to its hidden nature; it can lead to significant reduction in strength capacity of wire ropes over time, which can sometimes lead to their total or partial rupture. In order to optimize the residual resistance loss of a lifting wire rope, we propose a study of rupture impact of its wires on the loss of residual strength elastic. The results of tests allow a comparison between the loss of ultimate strength and residual strength loss residual elastic, so as to determine the normalized resistance and estimate the damage. The results of this work would be operated to establish the bond between reliability as being a statistical size and the damage by artificial damage observed and caused by cyclic requests.